Augmented fossil tour, an AR application for exploring and studying fossils - Liakopoulou, Dionysia; Giamali, Christina; Galanopoulos , Emmanuel; Kaddas , Panagiotis; Karydas , Nikolaos; Iakovidis , Alexandros; Paraskevopoulos , Konstantinos; Kontakiotis , George; Lyras , George; Besiou , Evangelia; Skampa , Elisavet; Panagiotopoulos , Ioannis P.; et al. (Bulletin of the Geological Society of Greece, 2024)
Fossils constitute a significant part of Earth's biodiversity, holding considerable heritage value. With an aim of improving and enhancing dissemination of knowledge and by integrating augmented reality technologies, this paper presents an AR application to identify fossils in two fossil sites, that of Agia Marina (Aegina Island) and Rafina (Attiki peninsula). An application compatible to mobile devices that enables the user to identify the fossils in situ, promoting learning through interactive experiences. It offers virtual tours that transport users back in time to the paleo environments where these fossils were originally found. This application seeks to make science, and especially paleontology, accessible and engaging to a wide range of people. To achieve this, we employed advanced photogrammetry techniques. By utilizing these methods, we were able to create detailed and accurate 3D models of marine fossils and environments. This approach not only enhances the visual representation of these paleo-environments but also provides precise data for scientific analysis and educational purposes. The AFT project allows us to capture the intricacies of invertebrate species and their habitats, ensuring that their importance within the marine ecosystem is effectively communicated and appreciated by a wider audience.